(untitled) (AYUSHDHARA, 2025)
Vandhyatva (female infertility) is a complex, multifactorial condition influenced by anatomical abnormalities, physiological dysfunctions, and psychosomatic factors. In Ayurveda, successful conception is dependent on the proper functioning and integration of Garbhasambhava Samagri- Ritu (timely ovulation), Ksetra (healthy uterine environment), Ambu (adequate nourishment), and Bija (viable gametes)- as well as the balance of Dosas, Dhatus, Agni, and Srotas. This review aims to provide an integrative anatomical framework for the clinical management of Vandhyatva by correlating Ayurvedic concepts with modern reproductive anatomy. Key anatomical structures such as Artavavaha Srotas (fallopian tubes), Beejagranthi (ovaries), and Garbhashaya (uterus) are examined in relation to their Ayurvedic counterparts and their roles in fertility. The review also discusses how Dosic imbalances- particularly in Vata and Pitta- can disrupt reproductive physiology and lead to infertility. Therapeutic approaches including Uttara Basti, Pancakarma, Rasayana, and Vajikarana therapies are explored for their potential in restoring reproductive health by rejuvenating anatomical integrity and functional harmony. The scope of this article includes a comparative anatomical analysis, integration of classical Ayurvedic texts with contemporary scientific literature, and the synthesis of evidence-based practices for individualized treatment strategies. This integrative approach offers a holistic, patient-centered model for infertility management, aiming to bridge traditional wisdom with modern biomedical insights for improved reproductive outcomes.